ウミタカスズキ NOTOTHENIA ROSII MARMORATA FISCHER ヨウギョ ノ セツジ コウドウ - 星合, 孝男; ホシアイ, タカオ; HOSHIAI, Takao (国立極地研究所, 1979)
P(論文) 1973年1月末,サウスジョージアにあるイギリス観測隊の基地で,ウミタカスズキ幼魚の摂餌行動を観察した.常には底生生活を営み,底生生物を摂取しているウミタカスズキ幼魚が,夜間,桟橋の照明に集った大型動物プランクトンをねらって水面直下にまで浮上し,泳ぎ回っている動物を捕食するのを観察した.胃内には幽門部から噴門部へかけて,エビの1種Chorismus antarcticusと端脚類,多毛類の1種Neanthes kerguelensisの遊泳生殖個体,ウミタカスズキならびにBathydraconidae sp.を主とした稚魚が,それぞれ団塊となって詰っていた.胃内容物とプランクトン相とを比較したところ,ウミタカスズキ幼魚は,プランクトン動物の中から,より大型な動物を選択的に捕食したものと考えられた.また,幼魚が捕食する対象は,ある程度の大きさであると同時に,魚の目の前で動くことが必要であるらしく思われた.このような行動を示した魚の胃内容物は,底に止っている個体の胃内容物とは異なったものであった。 The feeding behavior of juveniles of Notothenia rossii marmorata was investigated by the examination of stomach contents of three fish and by the field observation. Juvenile Notothenia came to the lighted area of shallow beach and fed on the swimming animals attracted by the light in late January of 1973. Amphipods, Chorismus. Neanthes and fish fry were mainly eaten in this order from evening to midnight. Juvenile N. rossii marmorata preferred the largest or larger animals in a prey population. Stomach contents of 64 juveniles of bottom dwelling N. rossii marmorata were also examined. Gammarid amphipods, algae and Ctenophore occurred frequently in the stomachs. The juvenile fish captured not only swimming animals but also swaying algae and Ctenophore. departmental bulletin paper